INSENTIF NON–FISKAL DALAM PERATURAN PEMERINTAH NOMOR 20 TAHUN 1994 MERUPAKAN PELUANG BAGI MUNCULNYA KEJAHATAN KORPORASI YANG TIDAK TERKENDALI - Retno Hendrati Purwaningrum (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
To all foreign investor, good incentive having the character of fiscal and also which non-fiskal, it is true cannot be quit of problem accompanying, and surely if attributed to its function as one of effort to reach the target of national development Indonesia, which actually represent the opportunity for appearance of corporation badness which do not in control which can be felt concerned about to become one of cause will not reach of target of national development Indonesia.in consequence Indonesia very depend onness foreign investor. In this case, existence PP. 20/1994 really representing opportunity for appearance of corporation badness which do not in control, so that can be felt concerned about to become the cause will not reach of target of national development Indonesia. Real correct in the reality, that Governmental Regulation Number 20 year 1994 the, needing correction again.